Mu opioid receptor expression is increased in inflammatory bowel diseases: implications for homeostatic intestinal inflammation. Issue 6 (18th November 2005) - Philippe, D; Chakass, D; Thuru, X; Zerbib, P; Tsicopoulos, A; Geboes, K; Bulois, P; Breisse, M; Vorng, H; Gay, J; Colombel, J-F; Desreumaux, P; et al.
Abstract : Background and aims: Recent studies with μ opioid receptor (MOR) deficient mice support a physiological anti-inflammatory effect of MOR at the colon interface. To better understand the potential pharmacological effect of certain opiates in inflammatory bowel diseases (IBD), we (1) evaluated the regulation in vivo and in vitro of human MOR expression by inflammation; and (2) tested the potential anti-inflammatory function of a specific opiate (DALDA) in inflamed and resting human mucosa. Patients and methods: Expression of MOR mRNA and protein was evaluated in healthy and inflamed small bowel and colonic tissues, isolated peripheral blood mononuclear cells and purified monocytes, and CD4 + and CD8 + T cells from healthy donors and IBD patients. The effect of cytokines and nuclear factor κB (NFκB) activation on MOR expression in lymphocyte T and monocytic human cell lines was assessed. Finally, DALDA induced anti-inflammatory effect was investigated in mucosal explants from controls and IBD patients. Results: MOR was expressed in ileal and colonic enteric neurones as well as in immunocytes such as myeloid cells and CD4 + and CD8 + T cells. Overexpressed in active IBD mucosa, MOR was significantly enhanced by cytokines and repressed by NFκB inhibitor in myeloid and lymphocytic cell lines. Furthermore, ex vivo DALDA treatment dampened tumour necrosis factor α mRNA expression in the colon of active IBD patients. Conclusions: Given the increased expression of MOR and the ex vivo beneficial effect of DALDA in active IBD, natural and/or synthetic opioid agonists could help to prevent overt pathological intestinal inflammation.